Development of a Farm Level Vegetable Washing Machine - Seghal, V K; Arora, M (Journal of Agricultural Engineering, 2006)
Washing is the first essential primary process unit operation for value addition of vegetables at farm level as well as for processing. A stainless steel, portable, electric power (1 hp) operated vegetable washing machine was developed. The inner rotary drum of the washer is made of stainless steel with 1.5 mm thickness, 760 mm length and 620 mm diameter. The machine is provided with a timer and an electronic device to regulate precisely the rotational speed of the drum up to 60 rpm. The performance of the washing machine was evaluated in terms of capacity, bruising percentage and washing efficiency for various vegetables viz. carrot, potato, raddish, turnip, ginger, okra, tomato and spinach. The capacity of the machine at optimum washing parameters varied from 1-6 qph, depending upon the type of vegetable washed. The washing efficiency ranged from 90.2 to 95.5%.